Giuseppe Ricuperati. L’ateo virtuoso Per una storia dei sentimenti e una religione della memoria - Barbagallo, Salvatore (Études sur la Région Méditerranéenne, 2022)
By forming the sensitive horizon of our identity, feelings define the values that settle in our interiority, activate a kind of consciousness that acts on the unconscious and makes coexistence possible. Feelings thus become a hidden archive of our being, a cultural heritage that differentiates civilizations. This sedimentation of emotions gives shape to an important register on which the historian can unfold his own research and carry out his own considerations and hypotheses. In this sense, Giuseppe Ricuperati addresses the problem related to the nature of feelings with respect to the “process of civilization” and their declination within a secular ethic.